Market Access for Developing Country Exports : Selected Issues. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2002)
In this paper, the World Bank and the International Monetary Fund have drawn together available research findings on the benefits of trade liberalization as well as on the obstacles to trade-oriented development.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet